Networked Haptic Interaction to Implement "Hand in Hand" Human Motor Skill Training for Tank Gunnery. (19th February 2013) - Liu, Guanyang; Lu, Keke; Zhang, Yuru; Liu, Lingzhi
The "hand in hand" approach has been validated as effective in human motor skill training, such as handwriting, drawing, driving and so on. This paper proposes a networked haptic interaction system to simulate the "hand in hand" training scheme for tank gunnery which requires tank gunners to complete tasks accurately and quickly. In the haptic-based training system, a network connecting two haptic devices plays the role of putting hands together, based on which the algorithms of haptic guidance and correction in real-time are developed for skill transmission between experts and trainees. The manner in which the traditional spring-damper model plays a role for high speed and high precision skill training is focused upon, since accuracy and operating speed are both critical in tank gunnery. An unbalanced spring control scheme is presented to benefit experts in accurately regulating trainees' operations without considering whether trainees are obedient in doing so.